Applying Quantitative Molecular Tools for Virus Transport Studies: Opportunities and Challenges. Issue 6 (23rd May 2017) - Wong, Kelvin; Molina, Marirosa
Abstract: Bacteriophages have been used in soil column studies for the last several decades as surrogates to study the fate and transport behavior of enteric viruses in groundwater. However, recent studies have shown that the transport behavior of bacteriophages and enteric viruses in porous media can be very different. The next generation of virus transport science must therefore provide more data on mobility of enteric viruses and the relationship between transport behaviors of enteric viruses and bacteriophages. To achieve this new paradigm, labor intensity devoted to enteric virus quantification method must be reduced. Recent studies applied quantitative polymerase chain reaction (qPCR) to column filtration experiments to study the transport behavior of human adenovirus (HAdV) in porous media under a variety of conditions. A similar approach can be used to study the transport of other enteric viruses such as norovirus. Analyzing the column samples with both qPCR and culture assays and applying multiplex qPCR to study cotransport behavior of more than one virus will provide information to under‐explored areas in virus transport science. Both nucleic acid extraction kits and one‐step lysis protocols have been used in these column studies to extract viral nucleic acid for qPCR quantification. The pros and cons of both methods are compared herein and solutions for overcoming problems are suggested. As better understanding of the transport behavior of enteric viruses is clearly needed, we strongly advocate for application of rapid molecular tools in future studies as well as optimization of protocols to overcome their current limitations.